APLIKASI AHP SEBAGAI MODEL SPK PEMILIHAN DOSEN - Adriyendi Adriyendi; Rahmadi Rahmadi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2011)
This research is conducted to apply the Analytical Hierarchy Process (AHP) method applied as modelof Decision Support System in election instructor staff at STAIN Batusangkar. Data collected by throughobservation and interview done in shares of administration academic at college. Here in after data analyzed tolearn the pattern from method used and added with the reference from literature. Experiment done use theMicrosoft Excel/ Expert Choice software known that method can yield the optimal decision in election instructorstaff. There by the method recommended to be applied to getting optimal result.